Organic milk supply in Poland: market and policy developments. Issue 12 (21st October 2019) - Zuba-Ciszewska, Maria; Kowalska, Aleksandra; Manning, Louise; Brodziak, Aneta
Abstract : Purpose: Global demand for organic milk products gives an opportunity to Polish organic farmers and dairies to supply national, European Union and international milk markets. The purpose of this paper is to review the historic and contemporary changes in organic milk production and processing in Poland, in order to identify the main factors of influence and to propose the direction of future market and policy development in the sector. Design/methodology/approach: In this study, secondary data from a range of literature sources and databases are analysed. The Lorenz's concentration ratio is applied to the data derived to evaluate the degree of concentration of certified organic farms in the different regions of Poland and conclusions are drawn as a result. Findings: Organic dairy farm operations in Poland are small scale and territorially dispersed. Although there is some evidence of growing supply concentration, Polish processors of organic milk face multiple barriers to development not least a lack of continuity of supplies. Whilst global markets are of interest, the development of alternative, innovative food networks in Poland that focus on provenance, integrity and promoting the special health benefits of organic milk would be of value to the sector, but further cooperation and integration is essential to take advantage of these market opportunities. Originality/value: This research underpins the need for appropriate national policies in Poland for the development and actualisation of a dynamic organic milk supply system that delivers value to local, regional and international markets.